(untitled) (Al-Farooq Journal of Sciences, 2026)
The green economy is a model of economic development based on the concept of environmental economics. It aims for the optimal utilization of economic resources and the reduction of resource depletion by transitioning from a brown economy to a green economy. This transition is achieved through a focus on environmental remediation, including resource efficiency, waste management, and the reduction of air pollution. Criminal protection of the green economy against air pollution is the most important guarantee for the protection of legal rules in general, and environmental rules in particular. The Libyan legislator has stipulated these rules in the Penal Code and in environmental protection legislation. However, criminal protection has been weak because the legislator’s wording regarding the crime of air pollution deviates from the requirements of legislative drafting, particularly concerning the meaning of certain terms and the standards required for drafting legislation in environmental crimes. These crimes differ from traditional crimes in both their material and moral elements, necessitating a criminal penalty commensurate with the offense committed. We have outlined the mechanism for addressing this issue and the environmental remediation approach to reducing air pollution, which is considered one of the most dangerous forms of environmental pollution for the green economy.